2013
DOI: 10.1590/s1679-45082013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da aderência ao programa de reabilitação cardíaca em um hospital particular geral

Abstract: Objective:Identify the primary factors that influenced the participant in our cardiovascular rehabilitation program towards missing their therapy sessions, and to correlate those factors with age, cardiovascular risk, and motivation of our population.Methods:We conducted a retrospective study with 42 patients (69.15±13.93 years) participating in the cardiac rehabilitation program at a general hospital in São Paulo, through the analysis of two scales applied during the initial evaluation: Cardiac Rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
1
8
1
16
Order By: Relevance
“…McCarthy et al [35] reported that suffering from other diseases, a lack of insurance coverage, or financial concerns were barriers to patients’ adherence to the program. These findings correspond with the results reported by Mair et al [42] indicating that travel/labor dispute, personal/family problems, and low initial provision were main factors contributing to absenteeism from a CR program. According to Meng et al [43] the patient-centered self-management program might be more effective in certain self-management outcomes than a usual care education in both short- and long-term periods.…”
Section: Discussionsupporting
confidence: 92%
“…McCarthy et al [35] reported that suffering from other diseases, a lack of insurance coverage, or financial concerns were barriers to patients’ adherence to the program. These findings correspond with the results reported by Mair et al [42] indicating that travel/labor dispute, personal/family problems, and low initial provision were main factors contributing to absenteeism from a CR program. According to Meng et al [43] the patient-centered self-management program might be more effective in certain self-management outcomes than a usual care education in both short- and long-term periods.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to this study, Mair et al 10 described that the factors that most negatively influenced patients' adherence to CVR were situations related to the travel arrangements or working conditions. However, because it was performed in a private hospital in the city of São Paulo, possibly the population of this study had a higher socioeconomic level than the present study.…”
Section: Lack Of Medical Prescription 32 40%contrasting
confidence: 91%
“…7,8,9 Other authors, although they did this survey by the patients' view, did so in specific regions of Brazil, such as São Paulo and Rio Grande do Sul. 10,11 However, these regions do not reflect the reality of the Brazilian Northeast, which has distinct cultural and socioeconomic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The CR adherence tool, while valid, does not consider factors that may impede initial enrolment. 20 The Cardiac Rehabilitation Barriers Scale (CRBS) is arguably the most widely administered, [21][22][23][24][25][26][27] comprehensive and psychometrically validated tool to assess patient barriers to CR enrolment and participation from the patient to health system levels. 28 It was developed following a review of the literature and revised with input from healthcare providers including CR staff.…”
Section: Introductionmentioning
confidence: 99%